Youth development in rural library: ICT gratification as mediating effect - Samsuddin, Samsul Farid; Omar, Siti Zobidah; Mohamed Shaffril, Hayrol Azril (Malaysian Journal of Library and Information Science, 2018)
This study investigates the relationship between ICT facilities and behavioural factors with positive youth development among rural youth in Malaysia, considering gratification of ICT usage in rural library as the mediating effect. The youth in rural areas are inclined to involve in negative affairs due to non- established beneficial activities. Therefore, the government has taken initiatives to equip rural libraries with ICT facilities and services to support social and academic activities amongst youth. A total of 400 respondents comprising rural library users in Peninsular Malaysia aged between 15 to 40 years were surveyed through multi-stage cluster simple random sampling. A survey method was employed and the analysis was conducted using Structural Equation Modelling (SEM). The results revealed that gratification of ICT usage among youths in rural library do not significantly mediates the relationship between ICT and specific behavioural factors in positive youth development. The finding indicates that respondents were not entirely depending on ICT facilities provided in the rural libraries in their undertakings. This study highlights several implications and recommendations for policy makers and practitioners towards improving ICT provisions in rural libraries in Malaysia.